Women of vision histories in feminist film and video (Visible evidence, 2001)
"Alexandra Juhasz asked twenty-one women to tell their stories - women whose names make up a who's who (and who will be) of independent and experimental film and video. What emerged in the resulting conversations is a compelling (and previously underdocumented) history of feminism and feminist film and video, from its origins in the fifties and sixties to its apex in the seventies, to today." "Women of Vision is a companion piece to Juhasz's 1998 documentary of the same name. The book presents the complete interviews, allowing readers to hear directly the voices of these articulate, passionate women in an interactive remembering of feminist media history. Juhasz's introduction provides a historical, theoretical, and aesthetic context for the interviews." "Interviewees include: Pearl Bowser; Margaret Caples; Michelle Citron; Megan Cunningham; Cheryl Dunye; Vanalyne Green; Barbara Hammer; Kate Horsfield; Carol Leigh; Susan Mogul; Juanita Mohammed; Frances Negron-Muntaner; Eve Oishi; Constance Penley; Wendy Quinn; Julia Reichert; Carolee Scheemann; Valerie Soe; Victoria Vesna; and Yvonne Welbon."--BOOK JACKET.